FORENSIC DESCRIPTION OF CRIMES COMMITTED BY WOMEN (World Bulletin of Management and Law, 2023)
In this article, women's crime differs from men's crime in terms of quantity and quality, the nature of the crime and its consequences, the weapon used, the motive and purpose, participation in the crime, and other objective and subjective aspects. The existence of these differences also highlights the need to study the specific criminalistic description of crimes committed by women and to radically separate it from the general description of crimes, ie the criminalistic description of crimes committed by men
Keywords: crimes committed by women; forensic description of crimes; social; biological